EVALUASI KEBIJAKAN PENEMPATAN IBU KOTA KECAMATAN KEPULAUAN BOTANG LOMANG DI DESA BAJO - Mursid, Iksan (HOLISTIK, Journal Of Social and Culture, 2013)
Regional autonomy aims to give the more effective service to society. Therefore, with the existence of such autonomy, society is expected to get better welfare than before. The capital placement as the central service has an important role in accessing all the societyâ€™s need. In Government Regulation Number 19 of 2008 about District on Chapter II article 6 verse 2,Â  it is said that â€œ the nominated location of a capital should observe the spatial aspect, facilities availability, accessibility, geographical situation, demography, economy social, politic, and cultureâ€. Ignoring these aspects affect the deterioration of the service and the failure of a development. This research aims to evaluate the placement policy of district capital of Kepulauan Botang Lemang in Bajo Village. The result of this research shows that the placement of district capital of Kepulauan Botang Lomang decided in 2007 is still not satisfying societyâ€™s expectation. This is caused by the lack of deep understanding in placing the district capital of Kepulauan Botang Lomang in Bajo Village.Keywords: regional, autonomy, access